On the Links Among Face Processing, Language Processing, and Narrowing During Development. (15th March 2014) - Pascalis, Olivier; Loevenbruck, Hélène; Quinn, Paul C.; Kandel, Sonia; Tanaka, James W.; Lee, Kang
Abstract From the beginning of life, face and language processing are crucial for establishing social communication. Studies on the development of systems for processing faces and language have yielded such similarities as perceptual narrowing across both domains. In this article, we review several functions of human communication, and then describe how the tools used to accomplish those functions are modified by perceptual narrowing. We conclude that narrowing is common to all forms of social communication. We argue that during evolution, social communication engaged different perceptual and cognitive systems—face, facial expression, gesture, vocalization, sound, and oral language—that emerged at different times. These systems are interactive and linked to some extent. In this framework, narrowing can be viewed as a way infants adapt to their native social group.